Sistem Pakar untuk Mendeteksi Kerusakan Sistem pada UPS Powerware 9120 - Minda Mora Purba; Aep Saepul Mahali (JURNAL MITRA MANAJEMEN, 2014)
ABSTRACTDesigning and building en expert system that contains knowledge about many kind of problem ofUPS and handling. To see the system that is running the search solution on the problem in theUPS. And tries to give input in form of knowledge together in a computer application or system,commonly referred to a expert system. So that the effectiveness of work can be achieved.Keyword : Expert System, Forward Chaining, Uninterruptible, Power System